Semelfactives as atomic predicates - Trebisacce, Romina (2021)
The goal of this paper is to provide evidence in favour of the hypothesis that, regarding their internal temporal structure, semelfactive and achievement predicates are alike (i.e., both are atomic). In order to do so, I will study the readings these predicates obtain in two different contexts: when they are modifi ed by for-phrases and when they combine with a progressive operator. The conclusion will be that when combined with elements that operate over intervals, semelfactives trigger a special reading (the iterative one), because these elements cannot operate within their internal temporal structure.